2009
DOI: 10.1007/s11085-009-9148-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Corrosion Resistance of Fe–Al–Cr Alloys in Simulated Low NO x Environments

Abstract: Due to their excellent corrosion resistance, iron aluminum alloys are currently being considered for use as weld claddings in fossil fuel fired power plants. The susceptibility to hydrogen cracking of these alloys at higher aluminum concentrations has led researchers to examine the effect of chromium additions on the corrosion resistance of lower aluminum alloys. In this work, three iron aluminum alloys were exposed to simulated coal combustion environments at 500 and 700°C for short (100 h) and long (5000 h) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…. In heavily sulfidizing atmospheres where H 2 S is present, large amounts of iron based sulfide nodules are observed . In the present tests, H 2 S was not included in the gas mixture, but it must have likely formed due to the presence of S in the ash, under the low NO x atmosphere.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…. In heavily sulfidizing atmospheres where H 2 S is present, large amounts of iron based sulfide nodules are observed . In the present tests, H 2 S was not included in the gas mixture, but it must have likely formed due to the presence of S in the ash, under the low NO x atmosphere.…”
Section: Resultsmentioning
confidence: 81%
“…For instance, slurry aluminides have been exposed to steam for over 22,000 h in the bypass of a steam turbine at 640 °C and 180 bar without substrate degradation and under laboratory testing conditions (100% steam, 650 °C, 1 bar) the same coatings have reached 50,000 h of exposure (the test is still ongoing) . DuPont et al have also demonstrated that FeCrAl containing alloys exhibit an outstanding corrosion resistance in sulfidizing and oxidizing conditions due to the formation of a protective Al 2 O 3 scale stabilized by the presence of Cr .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation